Integrating Population Genetics With Long‐Term Environmental Monitoring to Evaluate and Guide Vernal Pool Creation for Amphibian Conservation - Declan M. Winters; Emily Wilson; Stephanie S. Coster; Megan B. Rothenberger (Ecology and Evolution)
ABSTRACT The decline of biodiversity, particularly among amphibians, is strongly associated with habitat loss and fragmentation. Vernal pools are a critical ecosystem for many pool‐breeding amphibians, but they are often overlooked in wetland protection guidelines. Mitigation efforts include vernal pool creation and restoration, but these efforts have varying success in replacing lost functions. This study investigates the success of created vernal pools through long‐term environmental monitoring of wood frogs and spotted salamanders (2014–2023) and integrates population genetics to assess the local population health of the wood frog. First, we monitored and compared environmental parameters and reproductive success of indicator species between natural and created pools in a Pennsylvania state park. We then used microsatellite loci to assess within‐ and between‐pool measures of genetic diversity, population structuring, and gene flow for wood frogs. We found two carefully designed created pools positively contributed to local amphibian population persistence by maintaining similar measures of genetic diversity as compared to natural pools. On the other hand, one poorly created pool was genetically distinct and acted as a population sink. Although our findings offer valuable insights, they are based on a limited sample and may not fully represent the broader landscape. However, by integrating genetic information into long‐term monitoring datasets, our interdisciplinary approach enhances our understanding of amphibian population dynamics in vernal pool ecosystems. Our findings imply that the most important factors for restoration practitioners to consider when creating or restoring vernal pools are hydroperiod (12–35 weeks), volume (> 50 m3), depth (≥ 30 cm), and surrounding forest land cover (> 60%). These variables are better predictors of indicator species success than pool type (i.e., natural or created). Ultimately, this study emphasizes the need to accompany restoration efforts with long‐term monitoring programs that can be used to make adaptive management decisions in an era of extreme environmental change.